Feverfew attenuates carbon tetrachloride-induced testicular damage in rats - Mohammad Mazani; Shokofeh Banaei; Lotfollah Rezagholizadeh (Shahrekord University of Medical Sciences, 2020)
Introduction: Feverfew is an herbal medicine with the traditional usage of treating several disorders. Some investigations have demonstrated that feverfew is an effective remedy for the prophylactic treatment of inflammatory conditions, migraine and menstrual disorders. Therefore, this study was arranged out to evaluate the protective or curative potentials of feverfew methanolic extract (FME) on carbon tetrachloride (CCl4) induced oxidative trauma in testis. Methods: In this experiment, male Wistar rats were divided into seven groups (n=6). Group I as a normal control received 1 mL/kg distilled water for 14 days orally and on the 14th-day olive oil (1.5 mL/kg, i.p.). Group II received 1 mL/kg distilled water orally for 14 consecutive days. Groups III, IV and V animals were pretreatment groups and treated with three different doses of FME (40, 80, and 120 mg/kg, p.o, respectively) for 14 days. All groups except group one, were also intoxicated with 1.5 ml CCl4 (i.p, in a 1:1 dilution with olive oil) on the 14th day. Groups VI and VII were post-treatment groups and received FME (80 and 120 mg/kg, p.o, respectively) at 2, 6, 24 and 48 h after CCl4 injection. Results: Injection of CCl4 significantly (P < 0.001) reduced antioxidant enzymes (SOD and GPx) and increased malondialdehyde when compared to the control group. Administration of FME significantly (P < 0.05) improved these alterations near to control rats. Conclusion: It is suggested that FME has the ability to protect testis against oxidative damage, possibly through antioxidant effects of its bioactive compounds.